Extração de R-ficoeritrina da macroalga Solieria filiformis pelo método de pressurização e avaliação in vitro da citotoxicidade em células cancerígenas e atividade antioxidante. - Sousa, Ana Carolina Sales Pereira de (2024)
Solieria filiformis is a red macroalgae cultivated on the Brazilian coast that present in its constitution several biomolecules of industrial interest, including R-phycoerythrin (R-PE). R-PE has been used in the food, pharmaceutical, cosmetic and nutraceutical industries with anti-inflammatory, antioxidant, anticarcinogenic properties, among others. Because of its complex structure, many extraction methods may not provide extracts with high yield or high purity, such as maceration and freezing and thawing. Furthermore, some of these methods may use toxic solvents, in addition to high energy consumption, such as ultrasound-assisted extraction and solvent extraction. For this reason, the extraction of high-value-added biocompounds using environmentally friendly technologies is particularly interesting. Based on this premise, the present study aimed to analyze the yield of R-PE extracted from the macroalgae Solieria filiformis through the pressurization method. The study was developed using two different methodologies. Methodology 1 evaluated two different samples (wet and freeze-dried macroalgae), focusing on evaluating the extraction time and biofunctionality of the protein, at a constant pressure of 500 bar. R-PE maximum yield was reached lyophilized seaweed structure after 360 min, obtaining 0.67 mg of R-PE per gram of dry biomass. Furthermore, the extracts showed anticancer activity in in vitro tests on the HL-60 (promyeloblastic leukemia) and HCT-116 (colorectal cancer) cell lines. Using freeze-dried algae, methodology 2 analyzed cell rupture over time in different solvents (ultrapure water and phosphate buffer), macroalgae particle size and pressure variation of 200, 500 and 800 bar with and without agitation. In this methodology, a new equipment determined by a recombination cell was analyzed. Maximum yield reached 22.53 ± 0.60 mg of R-PE per gram of dry biomass. The optimal extraction conditions were the macerated structure, combination of pressure at 500 bar with agitation. Under these conditions, R-phycocyanin (R-PC) was also extracted with a yield of 3.70 mg·g -1 . The biomolecule presented characteristic spectra of R-PE, fluorescence and α-helical structure as the predominant element of its secondary structure. The extracts showed antioxidant capacity, with 99.55% in the reduction of 2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals and 13.94% in the chelation of ferrous ions. Therefore, using a pressurized extraction method proved to be effective in increasing the yield of R-PE, being able to be an interesting industrial process for the extraction and formulation of biotechnological products.